Evaluating the effectiveness of climate information services on farmer preparedness for climate events in Zambia - Moyo, Martin; Mpofu, Nkululeko; Mutenje, Munyaradzi; Kakwasha, Keagan; Chinembiri, Evans (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
In summary, the effectiveness of CIS in Zambia was influenced by knowledge, access, gender dynamics, characteristics of the services demanded, and various socio-economic factors. To enhance the impact of CIS required targeted interventions that improved access, addressed gender inequalities, built trust, and ensured the information was tailored to meet the specific needs of smallholder farmers. Continued research and investment in climate information systems will be vital for equipping farmers to better cope with the challenges posed by climate change and variability.